Asymptotic behavior of entire functions of improved regular growth in the metric of $L^p[0, 2\pi]$ - R.V. Khats’ (Karpatsʹkì Matematičnì Publìkacìï, 2013)
We describe an asymptotic behavior of entire functions of improved regular growth with zeros on a finite system of rays in the metric of $L^p[0, 2\pi]$.